Unidade de ensino potencialmente significativa para o ensino de equação do primeiro grau - Santos, Taís Montelli dos (2023)
The present study, allocated to the research line Educational Practices in Science and Mathematics Teaching of the Postgraduate Program in Science and Mathematics Teaching at the University of Passo Fundo, aims to investigate the contributions of a didactic sequence, structured in the format of Potentially Significant Teaching Unit (UEPS), to promote meaningful learning of first degree equations. The problem that generated the investigation lies in the empirical finding and review of studies of the ineffectiveness of the teaching and learning process in equation, especially in Elementary Education, pointing to the need to propose methodological alternatives. In this way, we sought support from the Theory of Meaningful Learning, recommended by David Paul Ausubel, to answer the following question: what are the contributions of a didactic sequence, structured in the UEPS format, to promote meaningful learning of first-degree equations? ? Thus, a UEPS was created based on Trends in Mathematics Education, the National Curricular Parameters and the National Common Curricular Base. This UEPS was developed in 20 meetings throughout 2022, in a seventh-year elementary school class at a public school in the city of Passo Fundo, RS. With regard to the research developed, the investigation is characterized as qualitative and had the records in the researcher's logbook, the diagnostic assessment and the individual assessment of the participants as data collection instruments. The data was analyzed into the following categories: subsumers, predisposition to learn, progressive differentiation and integrative reconciliation, and application of knowledge in new contexts. The results of the analysis indicate the existence of underlying concepts related to algebra in the students' cognitive structure; who consequently had an interest in learning, carried out progressive differentiation and integrative reconciliation and applied the concepts studied in other contexts. Elements that indicate that the UEPS is capable of promoting evidence of significant learning on the topic studied. From this perspective, the study gave rise to support material for teachers, which consists of the educational product of this dissertation.